The role of the breast care nurse in patient and family care. Issue 21 (20th February 2017) - Luck, Lauretta; Chok, Harrison Ng; Scott, Nancy; Wilkes, Lesley
Abstract : Aims and objectives: To describe the role of the breast care nurse in caring for patients and families. Background: The breast care nurse is an expert clinical nurse who plays a significant role in the care of women/men and their families with breast cancer. The role of these nurses has expanded since the 1990s in Australia. Design: Descriptive study. Methods: An online survey was sent to breast care nurses using peak body databases ( n  = 100). The survey consisted of nineteen nurse roles and functions from a previous Delphi technique study. Nurses rated the importance and frequency of role elements using a five‐point Likert scale and four open‐ended questions relating to role. Results: There were 89 respondents. Most of the sample were from remote ( n  = 37, 41%) and rural areas ( n  = 47, 52%). The majority of responses regarding importance and frequency of the BCN role had a mean score above 4, which corresponds to 'moderately important' and 'occasionally as needed'. There were significant differences between the level of importance and frequency on 10 items. Four role themes arose from the thematic analysis: Breast care nurses as patient advocates, patient educators, care coordinators and clinical experts. Conclusions: This study delineated the important nurses role in caring for patients and families during a critical time of their life. Further, it details the important nursing roles and functions undertaken by these nurses and compared this to the frequency with which these nurses perform these aspects of their role. Relevance to clinical practice: This study further delineates the important role that the nurses play in caring for patients and families during a critical time of their life. It extends further the frequency and importance of the supportive care and the need to educate their nurses on their role in providing spiritual care and research.